2007
DOI: 10.1136/bjsm.2006.031732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term treatment strategies over 4 weeks in Achilles tendinopathy

Abstract: Background: The therapeutic efficacy of non-surgical treatment strategies in Achilles tendinopathy (AT) has not been well clarified. Time-consuming and costly combinations of treatment for pain, physiotherapy and biomechanical procedures are often applied. Objective: To analyse the efficacy of single therapeutic regimens commonly used over a short period of 4 weeks. Methods: 31 male runners (mileage .32 km/week) with unilateral, untreated AT completed 4 weeks of either physiotherapy (10 treatments: deep-fricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 36 publications
0
85
0
2
Order By: Relevance
“…[17][18][19]24,35 Posterior tibialis and Achilles tendinopathies have been determined to improve from both types of arch-supporting orthoses plus exercise. 17,18,26 Orthoses provide arch support while maximizing tissue-specific strengthening to the muscle. 16 Likewise, the TCFO in the current study was used to provide arch support to offload the plantar fascia, while the stretches were used to restore and maintain normal tissue length.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19]24,35 Posterior tibialis and Achilles tendinopathies have been determined to improve from both types of arch-supporting orthoses plus exercise. 17,18,26 Orthoses provide arch support while maximizing tissue-specific strengthening to the muscle. 16 Likewise, the TCFO in the current study was used to provide arch support to offload the plantar fascia, while the stretches were used to restore and maintain normal tissue length.…”
Section: Discussionmentioning
confidence: 99%
“…Mayer and colleagues 85 conducted a 4-week study in which they randomly assigned runners with unilateral Achilles tendinopathy to 1 of 3 groups: (1) custom semi-rigid inserts (n = 9), (2) physical therapy intervention (n = 11), or (3) to a control group (n = 8). Subjects in each group were similar in age (inserts, 35  6.7 years; physical therapy, 41  5.9 years; control, 38  4.9 years), height, weight, as well as kilometers run per week (inserts, 50  13.5; physical therapy, 50  13.6; control, 53.1  10.6).…”
Section: Foot Orthosesmentioning
confidence: 99%
“…However, most are not supported by randomized controlled trials. Our objective was to review the evidence found in randomized controlled trials for conservative treatment of chronic (i.e., greater than three months' duration) midportion Achilles tendinopathy (Box 1 [13][14][15][16][17][18][19][20][21][22][23] ).…”
mentioning
confidence: 99%